IRC Mobile library Services - Gill Onesia Julio Simango, Gill Onesia (Universiti Teknologi PETRONAS, 2012)
The evolution of mobile technology allowed the introduction of m-learning. Many institutions have been implementing Digital Library Systems and more specifically m-library (Mobile Library). This report shows how libraries worldwide have been developing websites designed especially for mobile phones and PDA solutions, to enhance the accessibility range of their websites. It describes the Digital Library Systems available in the market, similarities among them and describes the proposed system to be implemented by UTP. Readers will be able to identify the major problems with regards to the IRC PRECISE System and the areas in which following worldwide practices or UTP’s needs the system can provide a more reliable link between IRC and students. This report aims to clarify and emphasize the importance of the development of this project and how relevant it is to the UTP Students Community and also to the IRC Management. The background specifies the scope of work for this project, the purpose and significance. The literature review presents studies that have been conducted in this area, and similar projects developed around the globe. Furthermore in this document, the methodology used to conduct research and the respective results and discussion are exposed; the timeline for the project completion, the tools identified for the project development will also be described in the methodology section. The final part describes the prototype including the functional specifications and lastly the conclusion which includes the relevancy of the objectives and recommendations.